IMPROVING STUDENT LEARNING OUTCOMES: BRAIN-BASED LEARNING WITH A MIND MAPPING MODEL AFTER THE COVID-19 PANDEMIC - Subiyantoro; Dicky Artanto; Afiq Fikri Almas (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2022)
This article examines related learning methods that can attract learners to learn the subjects of the Curriculum with a brain-based learning approach or brain-based Learning. This method uses field research at Muhammadiyah 1 Prambanan Junior High School by interviewing several respondents, namely representatives of 7th-grade students, field observation, and documentation analysis using data in the form of documents and related data sources needed. Data analysis using Miles and Huberman methods is by data collection, data reduction, presentation of data, and withdrawal of conclusions or data verification. The research results show that the learning process with a brain-based learning approach with mind mapping methods significantly impacts learners' learning interest in the subjects of The Islamic Civilization (Tarikh) in Grade 7. The trial results showed that almost all pupils' grade scores increased, affecting average grades in each class. The learners' enthusiasm is also seen when they do mind mapping with great earnestness. However, in this learning model with mind mapping, some shortcomings exist. Namely, it will be difficult for students who are not interested to understand the material quickly.